THE INFLUENCE OF ENDORSERS, PRODUCT QUALITY & WORD OF MOUTH ON CUSTOMER SATISFACTION THROUGH BRAND ATTITUDE (STUDY ON KAHYANGAN COFFEE PRODUCTS IN JEMBER REGENCY) - Purwanto, Arik; Hermawan, Haris; Sanosra, Abadi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of endorsers, product quality, and word of mouth on brand attitude and consumer satisfaction of Kopi Kahyangan in Jember Regency. In addition, this study also examines the role of brand attitude as an intervening variable in the relationship between endorsers, product quality, and word of mouth with consumer satisfaction. Expectation-Confirmation Theory (ECT) is used as a theoretical basis to understand how consumers' initial expectations are formed and influence satisfaction after consumption. Method: The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to Kopi Kahyangan consumers in Jember Regency. The sample in this study was selected using a purposive sampling technique, and data analysis was carried out using Structural Equation Modeling (SEM) with SmartPLS 4.0. The research model tests direct and indirect relationships between variables to understand the patterns of influence that occur. Results: The results of the study indicate that endorsers, product quality, and word of mouth have a significant influence on brand attitude and consumer satisfaction. In addition, brand attitude has a significant effect on consumer satisfaction. However, brand attitude does not act as a significant intervening variable in the relationship between external factors and consumer satisfaction. In other words, consumer satisfaction is more influenced by product quality and word of mouth factors than by brand image formed from external factors. Novelty: The novelty of this study lies in the use of Expectation-Confirmation Theory (ECT) in the context of local coffee product marketing, especially in seeing how external factors shape initial expectations that then affect customer satisfaction. The implications of this study emphasize the importance of focusing on real consumption experiences in increasing customer loyalty. The results of this study can be a basis for business actors in designing marketing strategies based on consumer experience and customer engagement to increase brand competitiveness in local and national markets.